Study of the antimicrobial activity of cationic carbosilane dendrimers against clinical strains of multidrug-resistant bacteria and their biofilms - Hernando-Gozalo, Marcos; Aguilera-Correa, John Jairo; Rescalvo-Casas, Carlos; Seijas-Pereda, Laura; García-Bertolín, Carlos; de la Mata, Francisco Javier; Sánchez-Nieves, Javier; Cuadros, Juan; Pérez-Tanoira, Ramón (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Antimicrobial Resistance is a serious public health problem, which is aggravated by the ability of the microorganisms to form biofilms. Therefore, new therapeutic strategies need to be found, one of them being the use of cationic dendritic systems (dendrimers and dendrons). Methods The aim of this study is to analyze the in vitro antimicrobial efficacy of six cationic carbosilane (CBS) dendrimers and one dendron with peripheral ammonium groups against multidrug-resistant bacteria, some of them isolated hospital strains, and their biofilms. For this purpose, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC) and minimum eradication biofilm concentration (MBEC) studies were carried out. In addition, the cytotoxicity on Hela cells of those compounds that proved to be the most effective was analyzed. Results All the tested compounds showed in vitro activity against the planktonic forms of methicillin-resistant Staphylococcus aureus and only the dendrimers BDSQ017, BDAC-001 and BDLS-001 and the dendron BDEF-130 against their biofilms. On the other hand, only the dendrimers BDAC 001, BDLS-001 and BDJS-049 and the dendron BDEF-130 were antibacterial in vitro against the planktonic forms of multidrug-resistant Pseudomonas aeruginosa, but they lacked activity against their preformed biofilms. In addition, the dendrimers BDAC-001, BDLS-001 and BDSQ-017 and the dendron BDEF-130 exhibited a good profile of cytotoxicity in vitro. Discussion Our study demonstrates the possibility of using the four compounds mentioned above as possible topical antimicrobials against the clinical and reference strains of multidrug-resistant bacteria.